(untitled) (Bangladesh Journal of Otorhinolaryngology, 2012)
Objective: To determine the clinicopathological features of fungal rhinosinusits at a tertiary care hospital. Material and Methods: This study was conducted at the Department of ENT, Head and Neck surgery, PGMI/ LRH Peshawar. This was a four years prospective study from January 2007 to December 2011. All fifty five patients were evaluated thoroughly in terms of history, examination and investigation. Biopsy of nasal mass was performed and biopsy specimens were studied by same histopathologist. After diagnosing the patient as a case of fungal rhinosinusitis surgical procedure was performed according the extent of disease. The data was analyzed using SPSS version 17. Results: These patients were in age range from 11- 66 years with mean age of 37.74 + S.D 16.46 years. They constitute 34 male and 21 female with male: female ratio was 1.6:1. Majority of patients (41.8%) belonged to middle age group. Most of the patients (60%) had lower socioeconomic status and mainly they were from rural area (74.54%) with only 30.9% literacy level. The commonest symptoms of these patients were nasal stuffiness (85.45%). Noninvasive fungal rhinosinusits was on top (87.27%). Aspergillus sp was the common fungal isolates (12.72%). Conclusion: Fungal rhinosinusitis is commonly affecting middle age group people. Allergic fungal rhinosinusitis is the most common entity of fungal rhinosinusitis and Aspergillus is the commonest pathogen. DOI: http://dx.doi.org/10.3329/bjo.v18i1.10414 Bangladesh J Otorhinolaryngol 2012; 18(1): 48-54